A new approach in modelling of hitch joint of a tractor semi-trailer using virtual Pacejka tyre model - Harun, Mohamad Hafiz; Hudha, Khisbullah; Mohd Samin, Pakharuddin; Abu Bakar, Saiful Anuar; Abd Kadir, Zulkiffli (Inderscience Publishers, 2021)
In this study, a new approach in modelling of hitch joint of a tractor semi-trailer is proposed by adopting virtual Pacejka tyre model. The virtual Pacejka tyre model is connected with a 16 DOF tractor semi-trailer combinations in Matlab-Simulink software and verified using validated software known as TruckSim. Two sets of simulations are conducted in the verification process which involves a double lane change (DLC) and steep steer cornering (SSC) test. It is observed from the results that by modelling hitch joint as a virtual Pacejka tyre model, the behaviour of the developed model closely follows the behaviour of the validated TruckSim model.